ANALISIS SENSORI PRODUK SOSIS SAPI KOMERSIAL MENGGUNAKAN PRINCIPLE COMPONENT ANALYSIS - Ni Wayan Putu Meikapasa; Lalu Danu Prima Arzani (Faculty of Agriculture Science & Technology, 2022)
The sensory characteristics of a product are one of the factors that determine the level of consumer acceptance. This study aimed to provide an overview of the differences in the sensory characteristics of commercial beef sausages. The study used three different brands of beef sausages (SG, SV, and SV) from different producers. The sensory attribute testing was carried out by 75 panelists. The sensory attributes tested were texture, color, aroma, mouthfeel, and meatiness of the product. Data were analyzed using one-way analysis of variance (ANOVA) with a confidence level of 95% (?=0.05) and followed by the Duncan test. Furthermore, to determine the variables that determine the sensory attributes of the product, multivariate analysis with principal component analysis (PCA) was used. The results of the study showed that the